Dispositions, Virtues, and Indian Ethics - Raimondi, Andrea (Journal of religious ethics, 2024)
According to Arti Dhand, it can be argued that all Indian ethics have been primarily virtue ethics. Many have indeed jumped on the virtue bandwagon, providing prima facie interpretations of Hindu, Jain, and Buddhist canons in virtue terms. Others have expressed firm skepticism, claiming that virtues are not proven to be grounded in the nature of things and that, ultimately, the appeal to virtue might just well be a mere façon de parler. In this paper, we aim to advance the discussion of Indian virtue ethics. Our intent is not to provide a catch-all interpretation of the different Indian schools. Our goal is, more modestly, to offer a theory of virtues in Indian philosophies, as a framework for theorists and interpreters who see these diverse traditions as amenable to systematic virtue analysis. Our theory grounds virtues in the reality of genuine moral dispositions and in a system of beliefs where morality is understood as transformative in nature.